Chronic kidney disease in HIV populations: prevalence, risk factors and role of transforming growth factor beta (TGF-߀1) polymorphisms - Ekrikpo, Udeme Ekpenyong (Department of Medicine, 2020)
Background and purpose: With the advent of antiretroviral therapy, HIV-infected individuals now live longer and are at increased risk of chronic kidney disease (CKD). Also, recent studies indicate a genetic predisposition to CKD in the African HIV population. This work investigated the prevalence of CKD (and its correlates) in the global and local HIV population and proceeded to investigate the diagnostic utility of urinary transforming growth factor-beta-1 (TGF-β1) for CKD in the HIV population and determine the association between polymorphisms of TGF-β1 gene and prevalent CKD. Methods: A meta-analysis was performed to document the prevalence of CKD in the global HIV population. From the local HIV population in Nigeria, the prevalence of CKD and traditional risk factors for cardiovascular disease was determined. Using ELISA, TGF-β1 levels was assayed in the urine samples of HIV patients with or without CKD to investigate the ability of urinary TGF-β1 to diagnose early CKD. SNP genotyping of rs1800469, rs1800470, rs1800471, rs121918282 in TGF-β1, rs60910145 (APOL1), rs73885319 (APOL1), rs71785313 (APOL1) and rs743811 (HMOX1) was performed using predesigned TaqMan genotyping assays. Results: Using meta-analytic methods, the global pooled CKD prevalence was 6.4% (95%CI 5.2–7.7%) with MDRD, and 4.8% (2.9–7.1%) with CKD-EPI. Among the WHO regions, Africa had the highest MDRD-based prevalence, 7.9% (5.2-11.1%) with the West African subregion carrying the heaviest burden, 14.6% (9.9- 20.0%). Among the local HIV population, using the CKD-EPI equation, the prevalence of CKD was 13.4% (11.6- 15.4%). Hypertension prevalence was 26.7% (25.5-28.0%); diabetes 5.6% (4.5-6.7%); obesity 8.3% (7.6-9.1%) and dyslipidaemia 29.1% (26.1-32.1%). HIV-infected individuals with CKD had significantly higher levels of urinary TGF-β1-creatinine ratio (uTGFβ1Cr) after controlling for potential confounding factors in regression models. However, within the CKD-HIV group, uTGFβ1Cr reduced as CKD stage worsened. The presence of APOL1 genetic risk independently increased the risk of CKD (OR 2.54, 95% CI 1.44-4.51) in the HIV population while the TGF-β1 SNP, rs1800470, appeared to have a protective effect (OR 0.44 (95% CI 0.20-0.97). There was no significant association between HMOX1 SNPs and CKD occurrence. Conclusion: There is a high prevalence of CKD (and other cardiovascular risk factors) in the adult HIVpopulation. Urinary TGF-β1 may be useful in the non-invasive detection of early CKD in the HIV population. Genetic testing may be used to predict the risk of CKD in the HIV population.